An application of Homotopy Perturbation Method (HPM) for solving Influenza virus model in a population - Topman *†, N.N.; Mbah†, G.C.E.; Collins†, O.C.; Agbata, B.C. (International Journal of Mathematical Analysis and Modelling, 2023)
This article examined application of Homotopy Perturbation Method (HPM) for solving influenza virus model. Some concepts and assumptions of homotopy perturbation method are discussed and homotopy perturbation method is used to solve differential equations with boundary conditions arising from influenza virus model. The total population is subdivided into eight epidemiological compartments in a homogenous and heterogeneous population. The obtained results as compared to those in existing literature is accurate. Analysis of the homotopy perturbation method showed that the method is flexible and very easy to understand